Developing Iraq's Security Sector The Coalition Provisional Authority's Experience - Rathmell, Andrew (RAND Corporation, 2005)
From May 2003 to June 28, 2004 (when it handed over authority to the Iraqi Interim Government), the Coalition Provisional Authority (CPA) worked to field Iraqi security forces and to develop security sector institutions. This book-all of whose authors were advisors to the CPA-breaks out the various elements of Iraq's security sector, including the defense, interior, and justice sectors, and assesses the CPA's successes and failures.